Adaptação do currículo nas aulas de língua portuguesa para alunos com deficiência intelectual - Guadagnini, Larissa (Universidade Federal de São Carlos, 2018)
Adapting of the regular curriculum, through adjustments, is an educational strategy that facilitates and promotes the learning of students with intellectual disabilities. The curricular adaptations in the Portuguese Language classes make the contents of this area less distant from the reality of the students with intellectual disability, since because of their pathology they are left aside in this discipline. Thus, the research aims to: (a) identify and describe the pedagogical practices of Portuguese language teachers addressed to the student with ID; (b) prepare and apply proposals for adaptation of activities of the Portuguese Language content for these students; (c) to evaluate from the perspective of the Portuguese Language teacher the applicability of the curricular adaptation register proposed in Resolution 61 of 2014 of the Government of the State of São Paulo. The researcher participated as a teacher of special education; a teacher of the discipline of Portuguese Language of the common class who teaches this discipline for two students with intellectual disabilities with a report, enrolled and frequent in the 7th year of Elementary School II, one of them student in the 7th grade class A and the other in the 7th grade class year D. From a qualitative approach, the research was characterized by being a participant, focusing on the interaction between the researcher and the members of the investigated situations, so that both parties could build new knowledge. In order to do so, this study covered four stages, namely: observations of the Portuguese language classes, initial interview, elaboration and application of adapted activities and final interview with the Portuguese Language teacher. It was used as an instrument for data collection: (a) observation script of the classes and; (b) interview script. The data were classified into categories, counting on the judges' appreciation to give reliability to the analysis made. The data were treated in a qualitative way using thematic categories. The results revealed that the pedagogical practice of the teacher was based on lectures, which inhibited the participation of students with intellectual disabilities, who were walking in the classroom. Factors such as these point to the need for training both to devise and to use adapted classroom activities. In the process of elaboration and application of the adapted curricular activities, it was observed the teacher's involvement as well as the participation of the students with intellectual deficiency in the classes, since, after the application of the adapted activities, the students began to participate in the classes, giving motivation to the teacher, who felt more responsible for their teaching and learning. Regarding the curriculum adaptive registration sheets proposed by the Government of the State of São Paulo in 2015, there was a need to reformulate the records, so that they become more functional and integrate the teachers' planning, not just a document completed and delivered in the school's coordination. The curriculum adaptation record should cover teaching strategies for students with intellectual disabilities, as well as instructions and materials for use by teachers. It is concluded, therefore, that planning and training actions are needed for teachers on how to make curricular adaptations.
Adaptations of the curriculum in Portuguese language classes for students with intellectual disabilities
Keywords: Educação especial; Adaptação curricular; Deficiência intelectual; Língua portuguesa; Special education; Curriculum adaptation; Intellectual disability; Portuguese language; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM